Precipitation balances deterministic and stochastic processes of bacterial community assembly in grassland soils. (May 2022) - Yang, Liyang; Ning, Daliang; Yang, Yunfeng; He, Nianpeng; Li, Xiangzhen; Cornell, Carolyn R.; Bates, Colin T.; Filimonenko, Ekaterina; Kuzyakov, Yakov; Zhou, Jizhong; Yu, Guirui; Tian, Jing
Abstract: Microbial biodiversity is crucial for maintaining ecosystem functions. As climate change progresses at both global and regional scales, there is a need to understand microbial community assembly processes and diversity to predict changes in soil function in different regions. However, our knowledge of the mechanisms that shape bacterial β diversity at multiple spatial scales with complex environmental gradients is very limited. To investigate the mechanisms driving bacterial β diversity at regional (across transects) and local (within transect) scales, soil samples were collected from 30 grassland ecosystems in three east-west transects in northern China. The regional species pools influenced β diversity by mediating rare taxa migration across the three transects. After correcting for regional differences in species, the importance of local community assembly processes in controlling bacterial diversity was independent of spatial scales. Homogeneous selection (HoS, 39%–60%) and dispersal limitation (DL, 31%–54%) proved to be the most important community assembly processes for soil bacteria. Two dominant bacterial taxa accounting for 65% of the total abundance were identified, mainly including Acidobacteria, Actinobacteria, and Proteobacteria, with 63% and 64% contributions for the HoS and DL, respectively. Mean annual precipitation (MAP) mediated the relative importance of deterministic and stochastic assembly in bacterial communities. Consistently across all spatial scales, the relative importance of DL increased with aridity, and the contribution of HoS decreased. Importantly, the relative abundance of the two dominant bacterial taxa controlled by the HoS and DL varied with MAP. Collectively, our results provide clear evidence that water availability mediates the community assembly process of soil bacteria. This conclusion is of utmost importance for predicting the dynamics of soil microbial diversity and nutrient cycling in natural ecosystems in drylands. Highlights: The migration of rare taxa affected β diversity across three transects. Homogeneous selection and dispersal limitation dominated bacterial assembly. MAP mediated the relative importance of deterministic and stochastic processes. The relative abundance of two dominant bacterial taxa co-varied with MAP. The pH was also crucial for the relative abundance of two dominant bacterial taxa.